Role of sex hormones in hypercapnia-induced activation of the locus coeruleus in female and male rats. (28th January 2016) - de Carvalho, D.; Marques, D.A.; Bernuci, M.P.; Leite, C.M.; Araújo-Lopes, R.; Anselmo-Franci, J.; Bícego, K.C.; Szawka, R.E.; Gargaglioni, L.H.
Highlights: Hypercapnia-induced c-Fos expression is not different between female and male rats. LC activation during CO2 challenge is not influenced by gonadal hormones in male rats. E2 plays an inhibitory role in the LC under room air conditions without altering CO2 responsiveness in females. Abstract: The locus coeruleus (LC) has been suggested as a CO2 chemoreceptor site in mammals. Most of the studies involving the role of the LC in hypercapnic ventilatory responses have been performed in males. Since ovarian steroids modulate the activity of LC neurons and females have a different respiratory response to CO2 than males, we evaluated the activity of LC noradrenergic neurons during normocapnia and hypercapnia in female and male rats with distinct sex hormone levels. Ovariectomized (OVX), estradiol (E2)-treated ovariectomized (OVX+E2) and female rats on the diestrous day of the estrous cycle were evaluated. Concurrently, males were investigated as gonad-intact, orchidectomized (ORX), testosterone (T)-treated ORX (ORX+T), and E2-treated ORX (ORX+E2). Activation of LC neurons was determined by double-label immunohistochemistry to c-Fos and tyrosine hydroxylase (TH). Hypercapnia induced by 7% CO2 increased the number of c-Fos/TH-immunoreactive (ir) neurons in the LC of all groups when compared to air exposure. Hypercapnia-induced c-Fos expression did not differ between diestrous females and intact male rats. In the OVX+E2 group, there was attenuation in the c-Fos expression during normocapnia compared with OVX rats, but CO2 responsiveness was not altered. Moreover, in ORX rats, neither T nor E2 treatments changed c-Fos expression in LC noradrenergic neurons. Thus, in female rats, E2 reduces activation of LC noradrenergic neurons, whereas in males, sex hormones do not influence the LC activity.